Pengaruh Konsentrasi Pemberian Pupuk Organik Cair Pomi Terhadap Pertumbuhan dan Hasil Pada Tanaman Bayam (Amaranthus sp.) - Bagus Putu Udiyana; I Made Sukerta; I Ketut Sumantra; I Dewa Gede Adiyoga Pranata (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2023)
The research aims to determine the effect of the concentration of POMI liquid organic fertilizer on the growth and yield of spinach plants. This study used a randomized block design with 6 treatments of POMI liquid organic fertilizer (5cc, 7.5cc, 10cc, 12.5cc, and 15cc) which were repeated 4 times to get 24 treatments. Based on the results of statistical analysis of the effect of the concentration of POMI liquid organic fertilizer on growth and yield of spinach plants, it was shown that there was a very significant effect on the parameters of plant height, number of leaves, leaf area, plant fresh weight and dry weight of spinach plants. The results showed that POMI liquid organic fertilizer with a concentration of 10cc / 990 ml of water (K3) was able to provide the best growth and yield compared to other treatments. The highest plant height was 46.7 cm, the highest number of leaves was 10, the highest leaf area was 827.422 cm², the highest plant fresh weight was 80.872 g, and the highest plant dry weight was 9.59 g